2023
DOI: 10.18240/ijo.2023.04.05
|View full text |Cite
|
Sign up to set email alerts
|

4D label-free proteomic analysis of vitreous from patients with rhegmatogenous retinal detachment

Abstract: AIM: To identify metabolites, proteins, and related pathways involved in the etiology of rhegmatogenous retinal detachment (RRD) for use as biomarkers in diagnosing and treating RRD. METHODS: Vitreous specimens were collected and liquid chromatography-tandem mass spectrometry analysis was performed using the four-dimensional label-free technique. Statistically significant differentially expressed proteins, gene ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway representations, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…7 mm, volume 3 ml, Sigma), concentrated by vacuum centrifugation, and reconstituted in 40 μl of 0.1% (v/v) formic acid. The peptide content was estimated by the UV light spectral density at 280 nm ( Huo et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 mm, volume 3 ml, Sigma), concentrated by vacuum centrifugation, and reconstituted in 40 μl of 0.1% (v/v) formic acid. The peptide content was estimated by the UV light spectral density at 280 nm ( Huo et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The integrated application of this technology not only greatly expands the coverage and resolution of protein detection but also enhances the dynamic range of analysis through improvements in time and spatial resolution, allowing researchers to capture subtle changes in protein expression. These changes could be key indicators of environmental stress ( Wang et al, 2021b ), changes in nutritional status ( Wang et al, 2023 ), or disease progression ( Huo et al, 2023 ). 4D label-free proteomics technology provides us with an unprecedented macroscopic perspective to comprehensively understand the biological traits of CGC at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this experiment is to address the problem of drug resistance after the widespread use of anti-VEGF therapeutic drugs. In our previous experiments, we have analyzed the vitreous fluid samples of patients with foramen ovale retinal detachment by 4D-DIA, and found that DEPs were mainly enriched in the cell adhesion pathway compared with the control group, and that DEPs were associated with the heat shock protein content, glycolysis, and acute inflammatory processes, which provided a reference for finding biomarkers for the pathogenesis of rhegmatogenous retinal detachment [9] . DDA technique, which is capable of capturing information on all acquired ions, reduces randomness in the detection process, has higher reproducibility and stability, and increased accuracy.…”
Section: Ppi Network Highlights Anti-vegf Treatment Responsementioning
confidence: 99%